Pengaruh Pemberian Reward terhadap Motivasi Belajar Matematika - Mewalo, Wulandari; Mubarik, Mubarik; Surahman, Surahman; Azizah, Azizah; Khairunnisa, Khairunnisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to determine the effect of giving rewards on the motivation to learn mathematics of class V students of SD Islam Alhidayah Besusu. The data analysis technique used in this study is the use of the Person Product Moment (PPM) Correlation formula. The results of the study after testing using the Person Product Moment correlation formula obtained the price of rxy0.642 greater than rtable0.09, namely 0.642>0.09, and seen from the guidelines for interpreting the correlation coefficient the value of rxy0.642 is in the coefficient interval value of 0.60 - 0.799 in that interval the level of relationship is strong, Conclusion, there is an effect of Giving Rewards on the Motivation to Learn Mathematics of Class V Students of SD Islam Alhidayah Besusu. This is evident from the results of hypothesis testing using the PPM (Person Product Moment) Correlation formula. Keywords: Effect of Giving Rewards, Learning Motivation, Class V Students, SD Islam Alhidayah Besusu